GA document 116 :. (Tokyo : A.D.A. edita, 2011)
- Jean Nouvel: Sofitel Vienna Stephansdom-Stilwerk, Vienna, Austria##- Jean Nouvel: ZAC Consuls de Mer + City Hall of Montpellier, Montpellier, France##- Jean Nouvel: Theater of Archipelago, Perpignan , Perpignan, France##- Oscar Niemeyer: Oscar Niemeyer International Cultural Center, Aviles, Spain##- Norman Foster: Faustino Winery, Ribera del Duero, Spain##- Peter Eisenman: City of Culture of Galicia, Santiago de Compostela, Spain##- Mansilla+Tunon: Lalin Town Hall, Lalin, Spain##- Eric Owen Moss: Samitaur Tower, Culver City, California, U.S.A.##- Steven Holl: Queens Library, Queens, New York, U.S.A.##-
boek
Keywords: Nouvel, Jean; Niemeyer, Oscar; Foster, Norman; Eisenman, Peter; Mansilla & Tunon; Holl, Steven; Moss, Eric Owen